Blink: An educational software debugger for Scratch - Strijbol, Niko; De Proft, Robbe; Goethals, Klaas; Mesuere, Bart; Dawyndt, Peter; Scholliers, Christophe (SoftwareX, 2024)
The process of teaching children to code is often slowed down by the delay in providing feedback on each student’s code. Especially in larger classrooms, teachers often lack the time to give individual feedback to each student. That is why it is important to equip children with tools that can provide immediate feedback and thus enhance their independent learning skills. This article presents Blink, a debugging tool specifically designed for Scratch, the most commonly taught programming language for children. Blink comes with basic debugging features such as ‘step’ and ‘pause’, allowing precise monitoring of the execution of Scratch programs. It also provides users with more advanced debugging options, such as back-in-time debugging and programmable pause. A group of children attending an extracurricular coding class have been testing the usefulness of Blink. Feedback from these young users indicates that Blink helps them pinpoint programming errors more accurately, and they have expressed an overall positive view of the tool.